2012
DOI: 10.1002/jsfa.5884
|View full text |Cite
|
Sign up to set email alerts
|

Screening of polyphenolic plant extracts for anti‐obesity properties in Wistar rats

Abstract: Only apple and cinnamon extracts were finally considered as potentially important anti-obesogenic extracts, due to their body fat-lowering effects, while the improvement of obesity-related metabolic complications by apple polyphenols highlights this extract as a promising functional food ingredient for the management of obesity and its metabolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…However, it could not be concluded that the enrichment in Erysipelotrichiciae detected in our study, is related to the host lipid and cholesterol phenotypes as we do not have biochemical data from these variables at the beginning of the study. Anyway, our group has previously reported a marked increase in body weight, subcutaneous and visceral fat depots due to the HFS diet in this experimental model that is accompanied by singular metabolic impairments (Boque et al, 2013). Therefore, it is likely that the metabolic derangement caused by the increased intake of fat and sugars given by the HFS diet could have produced a direct effect on this specific taxa.…”
Section: Discussionmentioning
confidence: 71%
“…However, it could not be concluded that the enrichment in Erysipelotrichiciae detected in our study, is related to the host lipid and cholesterol phenotypes as we do not have biochemical data from these variables at the beginning of the study. Anyway, our group has previously reported a marked increase in body weight, subcutaneous and visceral fat depots due to the HFS diet in this experimental model that is accompanied by singular metabolic impairments (Boque et al, 2013). Therefore, it is likely that the metabolic derangement caused by the increased intake of fat and sugars given by the HFS diet could have produced a direct effect on this specific taxa.…”
Section: Discussionmentioning
confidence: 71%
“…Earlier, we have reported reduction in the body weight of rats subjected to swimming training at 3 % intensity for 30 days [31]. Studies by Bais et al and Boque et al reported that supplementation with plant extract polyphenols decreased body weight gain in obese rats [32,33].…”
Section: Discussionmentioning
confidence: 72%
“…Usually, animal studies will be good models to try and establish lineal or final effects (Boque et al, 2013;de la Garza et al, 2011de la Garza et al, , 2013Etxeberria et al, 2012), although the results obtained must always be considered with caution, due to a lack of generalizability or extrapolation to the expected effects in humans. With regard to in vitro (Fernandez-Galilea et al, 2012;Garcia-Diaz et al, 2012;Prieto-Hontoria et al, 2013;Valdecantos et al, 2012) and ex vivo studies (Fanjul et al, 2015;Inigo et al, 2007;Larrayoz et al, 2006), these experiments are very useful for trying to discriminate the mechanisms of action by which a given food or food compound exerts the claimed effects.…”
Section: Previous Research and Evidence-based Decisionsmentioning
confidence: 99%